Emergency Peripartum Hystrectomy and Postnatal Depression - Tabinda Khalid; Sobia Nawaz; Malik Irfan Ahmed; Saima Nawaz Malik; Ruqyyah Salim; Shahla Manzoor (Journal of Rawalpindi Medical College)
Objective: to investigate postnatal depression after emergency peripartum hysterectomy versus controls.